STATUS MIKROBIOLOGI (TOTAL PLATE COUNT, COLIFORM, DAN Escherichia coli) SUSU KAMBING PERANAKAN ETAWA (PE) DI DESA SUNGAI LANGKA KECAMATAN GEDONG TATAAN KABUPATEN PESAWARAN - Hijriah, Pione Firbarama; Santosa, Purnama Edy; Wanniatie, Veronica (JURNAL ILMIAH PETERNAKAN TERPADU, 2016)
This research aimed to determine microbiologic status observation of the Ettawa Crossbred milk in Sungai Langka Village Gedong Tataan District Pesawaran Regency. This study used a survey method. Data retrieval in this research by questionnaire. The study was conducted from Mei—Juni 2016 in the Laboratory Veteriner Office of Lampung. The study used 15 samples from Ettawa Crossbred Goat in Sungai Langka Village Gedong Tataan District Pesawaran Regency. Parameters of microbiologic status observed total plate count, coliform, and E. coli. The result showed that 26,67% or 4 samples (KU-3, TH-1, TH-2, and TH-3) of milk sample had total plate count (TPC) excess of standard SNI, 83,33% or 11 samples of milk (Y-2, Y-3, KU-1, KU-4, TH-1, TH-2, TH-3, ED-1, ED-2 BD-1, and SK-1) had coliform excess of standard SNI, and 13,33% of milk sample had E.coli. Standard used the National Standardization Agency (NSA) 7388:2009 about the maximum limit of microbial contamination in milk. Keywords: Microbiological Status, Ettawa Crossbred Goat Milk, Microbial Contamination